W. Somerset Maugham's The razor's edge - Goulding, Edmund, 1891-1959.; Zanuck, Darryl Francis, 1902-1979.; Trotti, Lamar, 1900-1952.; Maugham, W. Somerset (William Somerset), 1874-1965.; Power, Tyrone, 1914-1958.; Tierney, Gene.; Payne, John, 1912-1989.; Baxter, Anne.; Webb, Clifton, 1889-1966.; Marshall, Herbert, 1890-1966.; Twentieth Century-Fox Film Corporation; Fox Video (Firm) (Beverly Hills, CA : FoxVideo, 1992)
Larry Darrell returns from World War I disillusioned with the Jazz Age values. He undertakes a quest in search of enlightenment which leads him to reject his fiancee, and his superficial lifestyle.
Videodisc release of the 1946 motion picture.
Based on the novel "The Razor's Edge" by W. Somerset Maugham.
"Catalog number 1049-80."
Producer, Darryl F. Zanuck ; director, Edmund Goulding ; screenplay, Lamar Trotti ; art directors, Richard Day, Nathan Juran ; photography, Arthur Miller ; editor, J. Watson Webb ; music, Alfred Newman.
Tyrone Power, Gene Tierney, John Payne, Anne Baxter, Clifton Webb, Herbert Marshall.
CLV extended play; chapter indexed; digital sound; mono.; CX noise reduction.
Keywords: Feature films -- United States; Video recordings for hard of hearing people; Videodiscs